Socio-Demographic, Dietary and Lifestyle Determinants of Central Obesity Among Adults in Java, Indonesia - Rizka Ramadhanti; Besral Besral (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Central obesity, with a global prevalence of 41.5%, is an escalating public health issue, particularly in developing countries such as Indonesia. Unhealthy diets and sedentary lifestyles contribute to energy imbalance and excessive fat accumulation. Few comprehensive studies have simultaneously examined the associations between socio-demographic, unhealthy dietary, and lifestyle factors with central obesity among the productive-age population in Java. This study aimed to identify the determinants of central obesity in this population. A cross-sectional design employed using secondary data from the 2023 Indonesia Health Survey (SKI). The study was conducted from February to June 2025 at the Faculty of Public Health, Universitas Indonesia. Data were analyzed using univariate, bivariate, and multivariable methods with complex sample analysis. The results showed that the prevalence of central obesity was 37.9%. Determinants that increase the risk of central obesity include older age (35-64 years) (AOR=2.034, 95%CI=1.955-2.116), female (AOR=4.257; 95%CI=4.038-4.488), higher education (AOR=1.313, 95%CI=1.268-1.361), employed (AOR=1.069, 95%CI=1.029-1.112), married (AOR=2.123, 95%CI=2.032-2.217), resided in urban areas (AOR=1.459, 95%CI=1.392-1.528), consumed fatty foods ≥1x/day (AOR=1.09, 95%CI=1.012-1.174), processed & preserved foods ≥1x/day (AOR=1.109, 95%CI=1.027-1.198), seasonings ≥1x/day (AOR=1.082, 95%CI=1.002-1.169), low (AOR=1.272, 95%CI=1.181-1.371) and moderate (AOR=1.216, 95%CI=1.137-1.301) physical activity. Meanwhile, several other significant factors, such as consumed sugary drinks, salty foods, and instant foods ≥1 time/day and 1–6 times/week, no daily fruit and vegetable intake, also smoking history, were found to be protective against central obesity. These results highlight the complexity of dietary and lifestyle influences on central obesity. Targeted interventions are needed for high-risk groups, and future longitudinal studies are recommended to establish better causal relationships.